Προβλήματα που προκύπτουν από τη διαχρονική εξέλιξη και τη συγχρονική χρήση του παρακειμένου [= Problems concerning the diachronic evolution and the synchronic use of the Perfect] - Αμαλία Μόζερ (Studies in Greek Linguistics 7, 1986)
This paper examines the relative status of the various forms of the Perfect in Modern Greek within the theoretical framework of Grammaticalization, arguing that only one of these, namely the ekho+infinitive form, is a genuine perfect periphrasis; it also deals with the implications that such an analysis would have for the explanation of the diachronic evolution of the Perfect.